TOWARDS MAQASID SHARIAH IN SUSTAINING THE ENVIRONMENT THROUGH IMPACTFUL STRATEGIES (International Journal of Islamic Business, 2020)
Maqasid Shariah requires the preservation of life on earth and with the relevance of environmental sustainability in protecting the earth and all life within it, the objectives of this paper is to investigate the strategies taken by a port in order to be environmentally sustainable and discuss it according to the principles of Maqasid Shariah. Qualitative research design was employed where data was collected through semi-structured interview with the officers in charge of environment at the company. Findings indicate that strategies implemented by the port have been successful in reducing emission and improve air quality which is an important step both to being environmentally sustainable and adhering to the Maqasid Shariah principles.